Construction and evaluation of a Salmonella minicell-based dendritic cell-targeted multi-epitope vaccine against Helicobacter pylori - Yang, Jiaxue; Chen, Kehan; Zhu, Yalan; Xie, Tiancheng; Fang, Chubin; Wang, Chuan; Tang, Tian (Frontiers in Immunology, 2025)
BackgroundHelicobacter pylori (H. pylori) infection is a global health concern linked to various gastrointestinal diseases, highlighting the urgent need for effective vaccines.MethodsIn this study, we developed two multi-epitope vaccine candidates based on Salmonella minicells: TA-2m and Apt-TA-2m. Apt-TA-2 is an advanced formulation of TA-2m, coated with dendritic cell-targeting RNA aptamer to enhance antigen delivery and immune activation. The physical properties of the vaccines, including shape, size, particle dispersion index (PDI), and zeta potential, were characterized using transmission electron microscopy (TEM) or dynamic light scattering (DLS). Comprehensive in vitro and in vivo evaluations were conducted to assess their safety, immunogenicity, and protective efficacy.ResultsBoth vaccines demonstrated excellent safety profiles and elicited strong immune responses, significantly reducing H. pylori colonization and alleviating gastric pathology. Notably, Apt-TA-2m demonstrated superior immunogenicity, characterized by enhanced T-cell cytokine production, increased mucosal IgA levels, and greater reductions in gastric bacterial loads.ConclusionsThese findings underscore the potential of minicell-based vaccines for combating H. pylori infections. The enhanced protective efficacy of the Apt-TA-2m vaccine positions it as a promising candidate for further clinical development.